2010
DOI: 10.1007/s12038-010-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus and tar hypothesis for squamous cell cervical cancer

Abstract: Human papillomavirus and tar hypothesis for squamous cell cervical cancerCervical cancer is the second most common life-threatening cancer among women worldwide, with incidence rates ranging from 4.8 per 100,000 in the Middle East to 44.3 per 100,000 in East Africa. Human papillomavirus (HPV) infection, especially HPV-16 and HPV-18, plays a major role in the etiology of cervical cancer, but HPV alone is not suffi cient to induce cancer. We propose that squamous cell cervical cancer is caused by an interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Genital infection with human papillomavirus (HPV), particularly the high-risk subtypes HPV-16 and HPV-18, is playing a major role in the etiopathogenesis of cervical cancer [ 3 ]; although the virus alone may not be sufficient to cause cancer [ 4 ], virtually all cervical cancers are associated with persistent infection with one of the high-risk types of HPV.…”
Section: Introductionmentioning
confidence: 99%
“…Genital infection with human papillomavirus (HPV), particularly the high-risk subtypes HPV-16 and HPV-18, is playing a major role in the etiopathogenesis of cervical cancer [ 3 ]; although the virus alone may not be sufficient to cause cancer [ 4 ], virtually all cervical cancers are associated with persistent infection with one of the high-risk types of HPV.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologists working in Honduras associated cooking over wood-burning stoves and CC ( Ferrara et al, 2000 ; Velema et al, 2002 ). We pursued this link with another ecologic study and demonstrated that the Pearson coefficient for solid fuel use and CC was 0.498 ( p < 0.05) ( Bennett et al, 2010 ), further supporting a role for inhaling smoke from sources other than tobacco as a cofactor in CC development.…”
Section: Coal Tar Related Risk Factors For Cervical Cancermentioning
confidence: 84%
“…While HPV is a major factor for developing CC, and given that persistent infection with a high-risk “oncogenic” type of HPV appears to be necessary for the development of invasive CC ( Walboomers et al, 1999 ; Munoz et al, 2003 ), a number of studies have shown that squamous cell CC may result from an additive or synergistic interaction between oncogenic HPVs and cervical tar exposures, a process generally referred to as co-carcinogenesis ( Haverkos, 2004 ; Working Group on the Evaluation of Carcinogenic Risks to Humans [IARC], 2004 ; International Collaboration of Epidemiological Studies of Cervical Cancer [ICESCC] et al, 2006 ; International Collaboration of Epidemiological Studies of Cervical Cancer [ICESCC], 2007 ). We highlight coal tar derivatives from cigarette smoking, tar-based vaginal sanitization products, and inhaled smoke from burning biomass (wood, coal, dung) in poorly ventilated kitchens, as potential co-carcinogenic factors that contain bioactive compounds likely to play a determinative role in CC development ( Rotkin, 1967 ; Winkelstein, 1990 ; Ferrara et al, 2000 ; Haverkos et al, 2000 , 2003 ; Velema et al, 2002 ; Steckley et al, 2003 ; Working Group on the Evaluation of Carcinogenic Risks to Humans [IARC], 2004 ; Haverkos, 2005 ; International Collaboration of Epidemiological Studies of Cervical Cancer [ICESCC] et al, 2006 ; International Collaboration of Epidemiological Studies of Cervical Cancer [ICESCC], 2007 ; Bennett et al, 2010 ). We identify published data from virological and genetic studies linking oncogenic papillomavirus genotypes and chemicals to development of cancer ( Rous, 1965 ; Prokopczyk et al, 2009 ; Wei et al, 2014 ).…”
Section: Human Papillomaviruses and Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations